2019
DOI: 10.1016/j.ajhg.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic GOT2 Mutations Cause a Treatable Malate-Aspartate Shuttle-Related Encephalopathy

Abstract: Early-infantile encephalopathies with epilepsy are devastating conditions mandating an accurate diagnosis to guide proper management. Whole-exome sequencing was used to investigate the disease etiology in four children from independent families with intellectual disability and epilepsy, revealing bi-allelic GOT2 mutations. In-depth metabolic studies in individual 1 showed low plasma serine, hypercitrullinemia, hyperlactatemia, and hyperammonemia. The epilepsy was serine and pyridoxine responsive. Functional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 38 publications
1
57
0
Order By: Relevance
“…Hence, the decreased aspartate in MSUD may affect oxidative phosphorylation and adenosine triphosphate production in neurons (reviewed elsewhere [ 15 ]). Furthermore, studies reported that MAS deficits are associated with infantile-onset epileptic encephalopathies [ 65 , 66 , 67 , 68 , 77 , 78 ] and autism [ 79 , 80 , 81 , 82 ]. In short, reduced aspartate levels in the CNS of MSUD patients may decrease MAS flux and contribute to neurologic symptoms in MSUD patients.…”
Section: Potential Impacts Of Decreased Brain N-acetylaspartate Anmentioning
confidence: 99%
“…Hence, the decreased aspartate in MSUD may affect oxidative phosphorylation and adenosine triphosphate production in neurons (reviewed elsewhere [ 15 ]). Furthermore, studies reported that MAS deficits are associated with infantile-onset epileptic encephalopathies [ 65 , 66 , 67 , 68 , 77 , 78 ] and autism [ 79 , 80 , 81 , 82 ]. In short, reduced aspartate levels in the CNS of MSUD patients may decrease MAS flux and contribute to neurologic symptoms in MSUD patients.…”
Section: Potential Impacts Of Decreased Brain N-acetylaspartate Anmentioning
confidence: 99%
“…The physiological relevance of mCAT is pointed by the fact that homozygous GOT2 -knock-out mice and zebrafish are not viable, as showed by van Karnebeek and colleagues [ 59 ]. In the same study it was reported that GOT2 (mCAT) bi-allelic mutations promote a mitochondriopathy through deficiencies in mCAT functioning.…”
Section: Cysteine Aminotransferase Structure and Localizationmentioning
confidence: 99%
“…In the same study it was reported that GOT2 (mCAT) bi-allelic mutations promote a mitochondriopathy through deficiencies in mCAT functioning. Despite showing residual mCAT enzymatic activity, affected patients present clinical evidence of this deficiency, including metabolic encephalopathy with epilepsy, progressive microcephaly, and several biochemical abnormalities [ 59 ]. Importantly, mutated mCAT promotes a dysfunctional malate-aspartate shuttle (MAS), which leads to a deregulation in the cellular NADH/NAD + equilibrium, affecting NAD-dependent enzymes and pathways [ 59 ].…”
Section: Cysteine Aminotransferase Structure and Localizationmentioning
confidence: 99%
See 2 more Smart Citations